Pengembangan Media Gambar Seri Puzzle untuk Meningkatkan Keterampilan Menulis Cerita Pendek Siswa Kelas III SDN Kalibata 11 - Salsabila Septiyani Satria; Robiatul Munajah (Global Action and Education for Society, 2026)
The development of series picture puzzle learning media is used to improve the short story writing skills of third grade students at SDN Kalibata 11. This study aims to explain the process of developing the series picture puzzle learning media and to determine its validity, effectiveness, and practicality in use. The type of research employed is Research and Development (R&D) using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research instruments include material validation sheets, media validation sheets, language validation sheets, and student response questionnaires. The results show that the material validation percentage is 97.77% with a very feasible category, the media validation percentage is 96.25% with a very feasible category, and the language validation percentage is 70% with a feasible category. In addition, the student response questionnaire results indicate that Class IIIA obtained a percentage of 94.87% and Class IIIB obtained 98%, both categorized as very feasible. The effectiveness of the learning media is also demonstrated by the N-Gain values of 0.54 for Class IIIA and 0.50 for Class IIIB, both of which fall into the moderate category. Based on these results, it can be concluded that the series picture puzzle learning media is feasible and moderately effective for teaching short story writing to third grade students at SDN Kalibata 11.